2019
DOI: 10.1111/apt.15088
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the critical role of dermatological events in patients with hepatocellular carcinoma treated with sorafenib

Abstract: Background: The positive results of the REFLECT trial in terms of survival (sorafenib vs lenvatinib) offer a new first-line option for hepatocellular carcinoma. Additionally, the expected results of immunotherapy could change the first-line treatment in hepatocellular carcinoma or the clinical trial design in first and second-line. Aims: To evaluate the impact of dermatologic adverse events under sorafenib in hepatocellular carcinoma patients as a clinical marker to predict prognosis and critically evaluate ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…Post hoc exploratory analyses of CORRECT and RESORCE indicate that patients with treatment-related HFSR had greater regorafenib benefit than those without; notably, a significant OS benefit was observed when HFSR occurred during the first treatment cycle, supporting continued treatment with dose adjustment [104,105]. Similar outcomes have been reported for regorafenib in the real-world REBECCA study [20], in the Japanese mCRC post-marketing surveillance study [23], and for the TKIs sorafenib and sunitinib in HCC and renal cell carcinoma [99][100][101]. Recently, early HFSR following sorafenib treatment in HCC has been associated with improved treatment response [106].…”
Section: Hfsr and Outcomessupporting
confidence: 52%
See 1 more Smart Citation
“…Post hoc exploratory analyses of CORRECT and RESORCE indicate that patients with treatment-related HFSR had greater regorafenib benefit than those without; notably, a significant OS benefit was observed when HFSR occurred during the first treatment cycle, supporting continued treatment with dose adjustment [104,105]. Similar outcomes have been reported for regorafenib in the real-world REBECCA study [20], in the Japanese mCRC post-marketing surveillance study [23], and for the TKIs sorafenib and sunitinib in HCC and renal cell carcinoma [99][100][101]. Recently, early HFSR following sorafenib treatment in HCC has been associated with improved treatment response [106].…”
Section: Hfsr and Outcomessupporting
confidence: 52%
“…One of the most common toxicities associated with TKIs, including regorafenib, is HFSR [96][97][98][99][100][101]. A published meta-analysis of regorafenib trials observed a clinically significant variation in all-grade regorafenib-related HFSR incidence across studied tumor types, with higher rates in patients with GIST (60%) versus HCC (50%) and mCRC (47%) [102].…”
Section: Hfsr and Outcomesmentioning
confidence: 99%
“…However, radiological tumor progression can be distinguished in four different patterns with a different impact on OS [39,40] . The key clinical question is when to move to second line treatment under tumor progression in a patient tolerating treatment or even more strikingly, if during treatment the patient has shown clinical benefit hallmarks such as dermatological events [41] . A new intrahepatic lesion has a better prognosis than a new extrahepatic lesion or a new vascular invasion [39,40] .…”
Section: Second Line Systemic Treatment: When and To Whom?mentioning
confidence: 99%
“…Methods. We analysed the prospectively collected data of consecutive patients who started sorafenib [5,6]. Thus, avoiding a definitive suspension of sorafenib in these patients would be extremely beneficial.…”
Section: Introductionmentioning
confidence: 99%